Reassessing standardized tests: Evaluating their effectiveness in school performance measurement - Oyeronke Christiana Paramole; Moses Adeleke Adeoye (Universitas Pendidikan Indonesia, 2024)
This research article reassesses the role of standardized tests in educational assessment, focusing on their complexities, historical context, and implications. It examines the accountability, and academic achievement benchmarks these tests provide while addressing criticisms such as cultural bias and narrowly teaching to the test. Alternative assessment methods, including formative and performance-based assessments, are also explored to offer a more holistic view of student learning and school performance. The article aims to contribute to a nuanced understanding of standardized tests' role in education, driving discussions on potential reforms that prioritize equitable and comprehensive assessment strategies. Critics raise concerns about the limitations of these tests, including their inability to capture the full range of student abilities, leading to biased and narrow educational outcomes. The study calls for a more balanced approach to educational assessment, integrating multiple methods to foster a more prosperous and fairer evaluation of student performance. Abstrak Artikel penelitian ini mengevaluasi kembali peran tes terstandarisasi dalam penilaian pendidikan, dengan fokus pada kompleksitas, konteks historis, dan implikasinya. Artikel ini membahas tolok ukur akuntabilitas dan pencapaian akademik yang dihasilkan oleh tes ini, sembari mengatasi kritik seperti bias budaya dan pengajaran yang hanya berfokus pada persiapan tes. Metode penilaian alternatif, termasuk penilaian formatif dan berbasis kinerja, juga dieksplorasi karena menawarkan pandangan yang lebih holistik terhadap pembelajaran siswa dan kinerja sekolah. Artikel ini bertujuan untuk memberikan kontribusi pada pemahaman yang lebih mendalam tentang peran tes terstandarisasi dalam pendidikan, serta mendorong diskusi mengenai reformasi yang memprioritaskan strategi penilaian yang adil dan komprehensif. Para kritikus mengkhawatirkan keterbatasan tes ini, termasuk ketidakmampuannya menangkap seluruh kemampuan siswa, yang menyebabkan hasil pendidikan yang bias dan sempit. Kata Kunci: Asesmen pendidikan; keadilan pendidikan; kinerja siswa; tes terstandarisasi